Using school-based early warning systems as a social and behavioral approach for HIV prevention among adolescent girls - DeSoto, Julie; Belsan, Asha; Wamala, Robert; Ochaya, Victor; Lulua, Rita Laura; Ekpo, Gloria; Cherian, Dennis; Benson, Shelby (Routledge Studies in Health in Africa, 2020)
A growing body of literature discusses social and behavioral approaches to HIV prevention. In a recent literature review of adolescent-focused HIV prevention research by Pettifor et al., (2018), the authors noted the need for combining HIV prevention strategies addressing individual, dyadic (peer/partner/parent), community (e.g. school environment), and societal- level risk and protective factors. In a systematic review of programs for HIV prevention among youth in sub-Saharan Africa, Harrison et al., (2010) concluded there should be emphasis on social risk factors for HIV, including gender, poverty, and alcohol, adding that future programs should work to change social norms and target structural factors contributing to HIV infection among adolescents. In 2008, Coates et al., called on the behavioral science community to better inform promising cognitive-behavioral, persuasive communications, and peer education approaches with theoretical frameworks. More recently, Govender et al., (2018) reviewed key challenges for mitigating HIV risk through sexual contact among young people in Eastern and Southern Africa (ESA), the region with the highest HIV burden. Overall, researchers and practitioners recommend that interventions focused on adolescents and young people should be developed using theoretical frameworks, contain multiple strategies, and comprehensively engage different levels of the ecosystem (schools, communities, individuals, families).
Keywords: School-based early warning systems; Social and behavioral approach; HIV prevention; Adolescent girls